Nomads as agents of cultural change the Mongols and their Eurasian predecessors (Perspectives on the global past, 2015)
Brings together a distinguished group of scholars from different disciplines and cultural specializations to explore how nomads played the role of ""agents of cultural change"". The comparative approach of this study, encompassing both a lengthy time span and a vast region, enables a clearer understanding of the key role that Eurasian pastoral nomads played in the history of the Old World